Combined Digital Methods for Solving Optimal Resource Allocation Problems - Hasmik S. Derdzyan (Изд-во НАН РА)
This article is devoted to the development of new effective methods for solving optimal resource allocation problems. The simulated annealing and genetic methods of digital optimization are widely used for solving these kinds of problems. Though these methods approach to the optimal solution of the problem, as usual, a long period of time is required for obtaining the exact solution. This article offers to combine the simulated annealing method with the modification of downhill simplex method to increase the convergence of the optimization method.
Keywords: Mathematics; Algorithm